2022
DOI: 10.7759/cureus.21069
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Vitamin D and Thyroid: An Enigma

Abstract: Hypothyroidism is a frequently encountered endocrine disorder in clinical practice. Besides its traditional role in bone health, vitamin D has been shown to have favorable effects in a variety of different systems due to its pleiotropic qualities and ubiquitous receptor expression. Over the years, researchers have been fascinated by the intricate molecular interplay between vitamin D and thyroid. In this regard, attempts have emerged to demonstrate the role of vitamin D in thyroid disorders. This article has r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 116 publications
(180 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, recent systematic reviews, meta-analyses, and meta-regression of observational studies [ 44 , 45 , 46 , 47 , 48 , 49 ] have confirmed that vitamin D levels were significantly lower in autoimmune hypothyroidism disease or HT patients compared to healthy people. Accordingly, it seems that there is proven evidence supporting a relationship between low vitamin D status and HT.…”
Section: Relationship Between Vitamin D Status and Hashimoto’s Thyroi...mentioning
confidence: 99%
“…Nevertheless, recent systematic reviews, meta-analyses, and meta-regression of observational studies [ 44 , 45 , 46 , 47 , 48 , 49 ] have confirmed that vitamin D levels were significantly lower in autoimmune hypothyroidism disease or HT patients compared to healthy people. Accordingly, it seems that there is proven evidence supporting a relationship between low vitamin D status and HT.…”
Section: Relationship Between Vitamin D Status and Hashimoto’s Thyroi...mentioning
confidence: 99%
“…The vitamin D will then be transported into the liver and adipose tissue. In the liver, vitamin D will be metabolized by 25-hydroxylase to obtain the 25(OH)D form as vitamin D inactive form [ 97 , 98 ].…”
Section: Toxicodynamicsmentioning
confidence: 99%
“…For example, the allele f of the FokI gene polymorphism leads to a longer VDR protein by inserting a start codon, which can affect VDR activity and reduces its effectiveness as a transcriptional activator. Also, the f allele has been correlated with higher 25(OH) vitamin D levels (22)(23)(24). Furthermore, it has been shown that VDR expression is negatively correlated with tumor malignancy, and is considered a biomarker for high-risk patients (23,24).…”
Section: Figure 2 Histopathologic Findings A) Papillary Thyroid Carci...mentioning
confidence: 99%
“…Also, the f allele has been correlated with higher 25(OH) vitamin D levels (22)(23)(24). Furthermore, it has been shown that VDR expression is negatively correlated with tumor malignancy, and is considered a biomarker for high-risk patients (23,24). VDR gene polymorphisms (ApaI, BsmI, TaqI, FokI) were also studied in order to establish their role as potential risk factors and predictors for tumor aggressiveness.…”
Section: Figure 2 Histopathologic Findings A) Papillary Thyroid Carci...mentioning
confidence: 99%